The biology of long-term denervated skeletal muscle - Bruce M. Carlson (PAGEPress Publications, 2014)
This review concentrates on the biology of long-term denervated muscle, especially as it relates to newer techniques for restoring functional mass. After denervation, muscle passes through three stages: 1) immediate loss of voluntary function and rapid loss of mass, 2) increasing atrophy and loss of sarcomeric organization, and 3) muscle fiber degeneration and replacement of muscle by fibrous connective tissue and fat. Parallel to the overall program of atrophy and degeneration is the proliferation and activation of satellite cells, and the appearance of neomyogenesis within the denervated muscle. Techniques such as functional electrical stimulation take advantage of this capability to restore functional mass to a denervated muscle.